Bureaucratic Reform Analysis: Effectiveness of BPJS JKN-Mobile Application in Realizing Public Satisfaction Reviewed from Comments on the Play Store Application - Novitasari, Indah; Muhlisoh, Lailatus Zayain; Maulana, Muhammad Syahul; Putra, Ilham Kurnia (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2025)
This study aims to identify the level of public satisfaction with bureaucratic reform carried out by the Social Security Administering Agency (BPJS) Health, especially through the implementation of the Mobile JKN application. In addition, this study analyzes the effectiveness of the Mobile JKN application in realizing public satisfaction with public services, by referring to user comments on the Google Play Store platform. The method used is a qualitative descriptive approach with a literature study research type, as well as data collection techniques based on sociological and empirical facts. The results of the study indicate that most users feel dissatisfied with the performance and quality of the Mobile JKN application service. The main complaints that arise include difficulties in accessing services and features that are considered not user-friendly. Based on these findings, it is hoped that BPJS Kesehatan can develop better applications in the future, with improved features that make it easier for the public to access health information and services digitally.